Glycosylation and Serological Reactivity of an Expression-enhanced SARS-CoV-2 Viral Spike Mimetic. Issue 2 (30th January 2022) - Chawla, Himanshi; Jossi, Sian E.; Faustini, Sian E.; Samsudin, Firdaus; Allen, Joel D.; Watanabe, Yasunori; Newby, Maddy L.; Marcial-Juárez, Edith; Lamerton, Rachel E.; McLellan, Jason S.; Bond, Peter J.; Richter, Alex G.; et al.
Graphical abstract: Highlights: HexaPro and 2P are recombinant glycoprotein versions of SARS-CoV-2 spike (S). HexaPro is an expression-enhanced version of SARS-CoV-2 S protein. Compared to 2P, HexaPro exhibits localised perturbations in glycosylation. Binding of antibodies from COVID-19 patients was insensitive to the glycoform of S. These results suggests that variations in S protein glycosylation will not impact serological studies. Abstract: Extensive glycosylation of viral glycoproteins is a key feature of the antigenic surface of viruses and yet glycan processing can also be influenced by the manner of their recombinant production. The low yields of the soluble form of the trimeric spike (S) glycoprotein from SARS-CoV-2 has prompted advances in protein engineering that have greatly enhanced the stability and yields of the glycoprotein. The latest expression-enhanced version of the spike incorporates six proline substitutions to stabilize the prefusion conformation (termed SARS-CoV-2 S HexaPro). Although the substitutions greatly enhanced expression whilst not compromising protein structure, the influence of these substitutions on glycan processing has not been explored. Here, we show that the site-specific N-linked glycosylation of the expression-enhanced HexaPro resembles that of an earlier version containing two proline substitutions (2P), and that both capture features of native viral glycosylation. However, there are site-specific differences in glycosylation of HexaPro when compared to 2P. Despite these discrepancies, analysis of the serological reactivity of clinical samples from infected individuals confirmed that both HexaPro and 2P protein are equally able to detect IgG, IgA, and IgM responses in all sera analysed. Moreover, we extend this observation to include an analysis of glycan engineered S protein, whereby all N-linked glycans were converted to oligomannose-type and conclude that serological activity is not impacted by large scale changes in glycosylation. These observations suggest that variations in glycan processing will not impact the serological assessments currently being performed across the globe.